Effective Proofread Strategies - Pondalos, Ezra Christina; Nugraha, Hendra (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2023)
Abstract In today's industrial sector, many companies are developing their markets both regionally and internationally. One of the ways they do this is to cooperate with regional and foreign companies. To make this happen, companies need documents using international languages or English. Apart from translating documents, currently document proofreading is also needed. This document proofreading aims to ensure that the document is good and correct to use or publish. This internship program is in cooperating with two partners there are PT. Indogaben Sukses Perkasa and UCLC UIB. Author assigned to translate legal documents for PT. Indogaben Sukses Perkasa and proofread academic articles for UCLC UIB. This program started on 08 February 2021 until 30 June 2021. This project done manually by author; it means that author did not use any computer assisted translation tool in translating the documents. The results of this project are five legal documents from PT. Indogaben Sukses Perkasa which is translated from Bahasa to English and five academic articles that already proofread by the author.